2012
DOI: 10.5343/bms.2011.1064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hook and Bait on Targeted and Bycatch Fishes in an Equatorial Atlantic Pelagic Longline Fishery

Abstract: We examined the effects of different hook style and bait type combinations on the catches of targeted, bycatch, and discarded fishes in equatorial atlantic waters. in total, 221 longline sets (>305,000 hooks) were deployed from portuguese pelagic longline vessels (sElEct-pal project) during the february-october fishing season. Three different hook styles and two bait types were tested: the traditional J-hook was compared to two circle hooks (one non-offset and one with 10° offset), and squid bait was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 4 publications
(7 reference statements)
11
63
2
Order By: Relevance
“…to avoid visual clutter, revealed that it fit well, with only two significant outliers: Coelho et al . () (significantly lower relative risk of capture on circle hooks than expected from the other studies) and Ariz et al . () (significantly high relative risk of capture on circle hooks than expected from the other studies) and three additional influential studies were Gilman et al .…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…to avoid visual clutter, revealed that it fit well, with only two significant outliers: Coelho et al . () (significantly lower relative risk of capture on circle hooks than expected from the other studies) and Ariz et al . () (significantly high relative risk of capture on circle hooks than expected from the other studies) and three additional influential studies were Gilman et al .…”
Section: Resultsmentioning
confidence: 67%
“…() (crocodile shark, Pseudocarcharias kamoharai ) and Coelho et al . () (bigeye thresher, Alopias superciliosus ) were atypical. Pelagic shark species found in either just oceanic habitats or both oceanic and coastal habitats other than blue shark were the main caught shark species for 9 of the 30 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other fisheries may use other types of hooks (e.g., circle hooks, tuna hooks, or a combination of different types). For some species, including the blue shark, J-style hooks have already been shown to cause higher hooking mortality rates than circle hooks (Carruthers et al 2009); however, for the elasmobranch species that are most frequently discarded (e.g., bigeye thresher, crocodile shark, pelagic stingray and manta rays) Coelho et al (2012) showed that the hook style (J-style vs. circle hooks) was unrelated to hooking mortality. The logistic models used in our study seem to be adequate for evaluating the contribution of potential explanatory variables (e.g., sex, region and specimen size) to the mortality odds-ratio estimates, even though the explanatory abilities of the final models are relatively low.…”
Section: Discussionmentioning
confidence: 96%
“…Our results suggest that circle hooks would reduce at‐vessel mortality in three ram‐ventilating sharks—oceanic whitetip, scalloped hammerhead and shortfin mako. This result is particularly promising for their management because these species are commonly caught in pelagic longline fisheries (Coelho, Santos, & Amorim, ), and their conservation status is a matter of international concern. A decrease in at‐vessel mortality for bycatch of these shark species does not necessarily translate to a decrease in post‐release mortality of released individuals, however, some proportion of post‐release mortality is related to physiological stress and injuries experienced during capture (Skomal, ).…”
Section: Discussionmentioning
confidence: 99%